Digital Repositories and Knowledge Management Practices in Higher Education Libraries - Sunil Kumar; Amandeep Kaur; Ketan B. Tiwari; Mamta; Divesh Sinha; Dr. Manpreet Kaur Dhanoa; Suruchi (International Journal of Scientific Research in Humanities and Social Sciences, 2026)
Digital repositories have become part of knowledge management practice in higher education libraries with repositories playing a critical role in institution knowledge creation, organization, preservation, and sharing. As the digital scholarship, open access initiatives, and research data management continue to grow very rapidly, academic libraries are turning to digital repositories as one of the ways to foster knowledge sharing, increase the visibility of research, and facilitate the teaching and learning processes. This paper will discuss how digital repositories are enhancing knowledge management behaviours in libraries of higher institutions of learning in terms of their relevance to the availability of information, institutional memory and scholarly communication. It further investigates the major issues like technological infrastructure, policy development, metadata standardization, user interaction and long term digital preservation. The article identifies best practices and strategic interventions that can help libraries fully integrate digital repositories in their knowledge management systems and therefore innovate and collaborate to create sustainable academic knowledge ecosystems.